2017
DOI: 10.1155/2017/6978984
|View full text |Cite|
|
Sign up to set email alerts
|

Urinary Exosomal MicroRNA Profiling in Incipient Type 2 Diabetic Kidney Disease

Abstract: Background Albuminuria is an early sign but not a strong predictor of diabetic kidney disease (DKD). Owing to their high stability, urinary exosomal miRNAs can be useful predictors of the progression of early-stage DKD to renal failure; fluid biopsies are ideal for detecting abnormalities in these miRNAs. The aim of this study was to identify novel differentially expressed miRNAs as urine biomarkers for type 2 DKD by comparing between patients of type 2 diabetes (T2D) with and without macroalbuminuria. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 42 publications
(47 reference statements)
0
71
1
Order By: Relevance
“…might provide a prognostic tool for DN. miRNA profiling of T2DM indicated significant upregulation of miR-877-3p in Type 2 macroalbuminuric than T2DMwhich was found to be associated with renal fibrosis 54. let-7c-5pupregulation in UE of DNP than controls associated with estimated GFR (eGFR) and advancement of DN 55.…”
mentioning
confidence: 99%
“…might provide a prognostic tool for DN. miRNA profiling of T2DM indicated significant upregulation of miR-877-3p in Type 2 macroalbuminuric than T2DMwhich was found to be associated with renal fibrosis 54. let-7c-5pupregulation in UE of DNP than controls associated with estimated GFR (eGFR) and advancement of DN 55.…”
mentioning
confidence: 99%
“…Although various miRs have been reported to be related to diabetic nephropathy, these results need to be cautiously interpreted. Some studies have identified miRs in cultured kidney cells [26], whereas others have analyzed urinary-exosomal miRs from patients who have simultaneously suffered from diabetes and CKD [27,28]. In cultured podocytes, high glucose was shown to induce podocyte dedifferentiation through the up-regulation of miR-193a [29].…”
Section: Discussionmentioning
confidence: 99%
“…Also, as many miRNAs have regulatory roles in both DKD and non‐DKD, single miRNA expression might exhibit poor specificity. Hence, there is an increase in studies utilizing urinary miRNA “biomarker panels”—multiple miRNAs measured in combination, to optimize diagnostic sensitivity and specificity as well as being more widely informative of disease processes . In a study by Argyropoulos et al, urine samples were assessed from a historical prospective cohort involving 906 eligible participants recruited from Children's Hospital of Pittsburgh in USA with a diagnosis of T1DM from 1950 to 1980.…”
Section: Quantification Of Urinary Mirnas As Biomarkers For Dkdmentioning
confidence: 99%